2015
DOI: 10.1063/1.4915936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interparticle plasmon coupling and temperature on the optical properties of bimetallic composite nanoparticles with a core-shell structure

Abstract: In this work, the optical properties of bimetal composite nanoparticles with a core-shell structure are investigated in the framework of quasi-static and Maxwell-Garnett approximation. The influence of interparticle plasmon coupling and temperature on the optical absorption of bimetallic core-shell nanoparticles is studied while the shell consists of Al and Cu particles. In fact, dependence of the optical absorption and its full width at half maximum on the dielectric constant of the core, host matrix, and emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Optical properties of nobel metal nano-structures have received great attentions due to their plasmonic properties, especially the optical absorption effects induced by localized surface plasmon resonance (LSPR) have attracted much attention in recent years [6,7]. The electrical field scattering problems could be solved with Laplace's equation for the potential [8,9], which is very similar to the solution of media sphere. The radius of dielectric-metal core-shell multi-layered nanosphere is 25nm in this study, which is smaller than the incident wavelength.…”
Section: The Classical Models Of Electromagnetic Fields and Waves Are...mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical properties of nobel metal nano-structures have received great attentions due to their plasmonic properties, especially the optical absorption effects induced by localized surface plasmon resonance (LSPR) have attracted much attention in recent years [6,7]. The electrical field scattering problems could be solved with Laplace's equation for the potential [8,9], which is very similar to the solution of media sphere. The radius of dielectric-metal core-shell multi-layered nanosphere is 25nm in this study, which is smaller than the incident wavelength.…”
Section: The Classical Models Of Electromagnetic Fields and Waves Are...mentioning
confidence: 99%
“…These three absorption peaks could be explained by the plasmon hybridization theory [7,11], dielectric-metal core-shell multi-layered nanosphere could be considered as a solid silver core inserted into a dielectric-silver nano-shell. LSPR can be considered as an interaction between the plasmon responses of a silver core with its energy mode 〉 | plasmon mode, the distribution of induced charges on the surface of silver core is oppositely aligned with plasmon of nano-shell, which reduces the dipole moment, so the absorption peak is too weak to be observed in experiments [8,9,11]. In order to make the plasmon modes of dielectric-metal core-shell multi-layered nanosphere understand fully, the distribution of local electrical field intensity at…”
Section: The Classical Models Of Electromagnetic Fields and Waves Are...mentioning
confidence: 99%
“…Zhu et al have reported the local dielectric environment dependent local field enhancement properties in double concentric silver nanotube using plasmon hybridization method and quasi-static calculation [20]. Daneshfar et al have studied optical and spectral tunability of multilayer spherical and cylindrical nanoshell with quasi-static theory [21]. Wu have studied the the refractive sensitivity of silver-dielectric-silver and gold-dielectricgold nanotube, and the result shows that the sensing ability can be improved by reducing the thickness of the inner gold shell or increasing the thickness of the outer gold shell [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…[20] Daneshfar et al have studied optical and spectral tunability of multilayer spherical and cylindrical nanoshell with quasi-static theory. [21] Wu et al have studied the multiple Fano resonance of nanrod and nanoring, which has been applied in refractive index sensing and high-sensitivity biosensors. [22] The optical absorption of three-layered nanoshell shows that the LSPR can be well adjusted the parameters of nanoshell.…”
Section: Introductionmentioning
confidence: 99%